Aegilops tauschii Accessions with Geographically Diverse Origin Show Differences in Chromosome Organization and Polymorphism of Molecular Markers Linked to Leaf Rust and Powdery Mildew Resistance Genes - Majka, Maciej; Kwiatek, Michał T.; Majka, Joanna; Wiśniewska, Halina (Frontiers in Plant Science, 2017)
Aegilops tauschii (2n=2x=14) is a diploid wild species which is reported as a donor of the D-genome of cultivated bread wheat. The main goal of this study was to examine the differences and similarities in chromosomes organization among accessions of Ae. tauschii with geographically diversed origin, which is believed as a potential source of genes, especially determining resistance to fungal diseases (i.e. leaf rust and powdery mildew) for breeding of cereals. We established and compared the fluorescence in situ hybridization (FISH) patterns of 21 accessions of Ae. tauschii using various repetitive sequences mainly from the BAC library of wheat cultivar Chinese Spring. Results obtained for Ae. tauschii chromosomes revealed many similarities between analyzed accessions, however some hybridization patterns were specific for accessions, which become from cognate regions of the World. The most noticeable differences were observed for accessions from China which were characterized by presence of distinct signals of pTa-535 in the interstitial region of chromosome 3D, less intensity of pTa-86 signals in chromosome 2D, as well as lack of additional signals of pTa-86 in chromosomes 1D, 5D or 6D. Ae. tauschii of Chinese origin appeared homogeneous and separate from landraces that originated in western Asia. Ae. tauschii chromosomes showed similar hybridization patterns to wheat D-genome chromosomes, but some differences were also observed among both species. What is more, we identified reciprocal translocation between short arm of chromosome 1D and long arm of chromosome 7D in accession with Iranian origin. High polymorphism between analyzed accessions and extensive allelic variation were revealed using molecular markers associated with resistance genes. Majority of the markers localized in chromosomes 1D and 2D showed the diversity of banding patterns between accessions. Obtained results imply, that there is a moderate or high level of polymorphism in the genome of Ae. tauschii determined by a geographical origin, which we proved by cytogenetic and molecular markers analysis. Therefore, selected accessions might constitute an accessible source of variation for improvement of Triticeae species like wheat and triticale.